Total quality management - Kumar, S.R.J. Shantha (Anuradha, 2011)
In-order to be an achiever one has to be quality conscious and be aware of the quality principles and concepts. This is what the book seeks to atain. It begins with the terminologies commonly used in TQM circles inorder to give an insight as to what TQM is all about, perhaps this is not a conventional approach, ironically, let alone the fact that TQM is also about doing common things in an uncommon way.